Oral tradition of the indigeniuos people: analyzing the self identity and perspectives on life of the semai community in Pos Dipang, Perak - Abdul Rahman, Azlan; Saad, Sharina; Abdul Aziz, Nurazila; Bidin, Samsiah (2011)
The teaching of 'ancient wisdom' of indigenous people is unique, valuable and has historical importance because it is passing down to its present inheritors through oral tradition. The Semai, who are the Senoi subgroup in the Semai lives scattered in the area surrounding Banjaran Titiwangsa, mainly in the middle of Perak, the southern part of Perak and in the west of Perak. In 1993 statistic there was an increase of more than 42,000 Semai and this figure shows that the Semai has the highest population and is the largest indigenous tribe in Malaysia. The Semai live in their own community consist of 60 to 300 people lead by a headman or popularly known as "Batin". The Semai have rich traditions of oral histories, folklore and mythology. Orang asli oral tradition is used mainly to amuse, to teach, to record, to remind, to explain and to impart important social and ethical mores to ensure community living and continuity to the younger generations. The Semai in Pos Dipang Perak practice oral traditions in imparting knowledge on how their beliefs in ancestors and supernatural power proven to be true. The Semai who are largely animists, are still influenced by their old beliefs and customs. The loss of such traditional knowledge will surely have an effect on the destruction of its heritage and culture. These unwritten stories, if left uncollected and unpreserved, the stories then one day will disappear forever. Therefore, this research aims to analyze an indigenous Malaysian's Semai telling of idiosyncratic Semai myth to analyze their sense of community, their perspectives on life, education, personal identity, and ancestral anchorage.